Geomapping methodology for the GeoCluster Mapping Tool to assess deployment potential of technologies for energy efficiency in buildings - Sesana, Marta Maria; Cuca, Branka; Iannaccone, Giuliana; Brumana, Raffaella; Caccavelli, Dominique; Gay, Charly (My University, 2015)
Energy efficiency in buildings will play a major role in responding to EU climate change and energy-saving policies, if sustainable actions are to be trigged at large scale involving EU, all Member States and their regional and local authorities. The objective of this paper is to explain the Geocluster methodology developed within the European "GE2O" project aimed at developing a general framework for the assessment of the effectiveness of building technologies for energy efficiency. The research aimed to locate similarities across the EU countries by combining parameters and indicators structures in homogeneous layers and sub-layers (i.e. building technology, context, policies and regulations, climatic conditions, social aspects) in order to develop a repository to be used as source of data for a dynamic geo-database web service. The assessment has been performed on two selected technologies, thermal insulation for envelope retrofitting and solar cooling, respectively, for two pilot areas: Benelux and Mediterranean arc. The final goal was to create an Open Source geo-portal named GeoCluster Mapping Tool, based on international standards in the GIS domain, which implements the methodology developed and becomes a decision-making tool for private or public parties.
Keywords: Building technologiesa; Energy efficiency; Geocluster methodology